Perbandingan Pengetahuan Tentang Vaksinasi Covid-19 pada Masyarakat yang Sudah Divaksin dengan yang Belum Divaksin Covid-19 - Muskhab Eko Riyadi; RR. Viantika Kusumasari; Dian Nur Adkhana Sari (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2023)
The impact of the Covid-19 pandemic is still a problem, many of the impacts caused by this virus, such as health problems, economy to death. One of the most effective efforts to reduce the impact of the pandemic is by vaccinating against Covid-19. The government also conducts socialization to increase public knowledge and understanding of the Covid-19 vaccine, which is because there are still many people who do not know about vaccines and they easily accept rumors and hoax news about the Covid-19 vaccine. This study aims to determine the difference in the score of knowledge between people who have not been vaccinated and people who have been vaccinated against Covid-19 in Caben, Sumbermulyo, Bambanglipuro, Bantul, DI. Yogyakarta. This research uses a comparative study design, the sample size is 90 respondents which are divided into 45 people who have not been vaccinated and 45 people who have taken the Covid-19 vaccine, the research instrument uses a questionnaire to measure knowledge about vaccination, the sampling technique uses consecutive sampling and statistical test using the Mann-Whitney test. The results showed that the average knowledge score of people who had not been vaccinated for Covid-19 was 45.22 and the average score of knowledge of people who had been vaccinated was 69.68, while the results of the Mann-Whitney test showed that there was a difference in the score of knowledge about vaccination between people who had not vaccinated against Covid-19  with people who have been vaccinated against Covid-19, with a p-value of 0.000. This study concludes that knowledge about Covid-19 vaccination in people who have been vaccinated is higher than people who have not been vaccinated against Covid-19